Frequency of Complicated gallstone disease & Role of Laparoscopic Cholecystectomy - Abdul Razaque Raza Qazi,Ubedullah Shaikh,Sikander Azam Yousfani, Farkhanda Jabeen Dahri , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2011)
OBJECTIVE: To determine frequency of complicated gallstone disease and role of laparoscopic cholecystectomy in a tertiary care hospital at Nawabshah. STUDY DESIGN: Prospective analytical study. PLACE AND DURATION OF STUDY: Surgical Unit-III at Peoples University Hospital Nawabshah, Sindh. Pakistan from August 2010 to July 2011. MATERIAL & METHODS: This study consisted of 100 consecutive cases of gallstone disease. Detailed History was taken from all the patients with special regard to the abdominal pain or pain in right hypochondrium, lump in right hypochondrium, vomiting, dyspepsia and fever. Clinical examination of right hypochondrium was especially examined for assessment of Murphy's sign, palpable mass, visceromegaly. Specific investigations especially ultrasound of abdomen was performed as diagnostic modality and for assessment of complicated gallstone disease (eg: thickness of wall of gallbladder, adhesions, empyma, and mucocele). All the patients went for laparoscopic cholecystectomy. Data was analyzed through SPSS software version 16.0. Results were prepared with help of tables and graphs. RESULTS: 100 consecutive cases of gallstone disease were enrolled. 81(81%) were female and 19(19%) were male; with felmale to male ratio of 4.26:1.The mean age was 32.78+2.4years. Symptoms of patients were pain in RHC was found 63(63%), pain in RHC associated with epigastrium was seen in 67(67%) cases, dyspepsia was 7(7%) and fever was 9(9%) cases. Ultrasound examination findings were single stone in 24(24%) patients, multiple stones in 76(76%) patients, impacted stone at the neck of gallbladder was found in 28(28%) patients, thick wall gallbladder in 48(48%) patients, empyma gallbladder 12(12%) patients, mucocele 5(5%) patients, contracted gallbladder 13(13%) patients, adhesion around gallbladder in 36(36%) patients and cirrhosis of liver in 3(3%) patients. The common complications seen in this study were nausea and vomiting in 22(22%), chest infection in 16(16%) , biliary leak 3(3%) patients and port site wound sepsis in 9(9%) patients .The duration of hospital stay varied from 1 to 3 days. majority 84(84%) were discharged within 2 to 3 days. The patients with complications and conversion had still longer stay. CONCLUSION: Laparoscopic cholecystectomy is a safe and successful procedure for complicated gallstone disease with low threshold ofconversion to open cholecystectomy.